First-Year Teachers' Dispositions: Exhibited and Perception of Being Taught - Shane Kirchner (The Advocate, 2013)
The NCATE standards adopted in 2000 mandated the assessment of teacher dispositions. However, the lack of specificity of the construct has led to an environment where many institutions struggle to develop high-quality disposition assessments. The result is a hodgepodge of constructs and systems; some that work, some that do not. This quantitative study used a modified version of the Teacher Disposition Index to identify the extent to which first-year teachers self-reported exhibiting the dispositions and whether they perceived they were taught the dispositions by the teacher education programs from which they graduated.